Impact of road infrastructure and exports on regional economic growth case of region Ancash - De La Cruz Pairazamán Rodas, Alejandro (2018)
This investigation work evaluates infrastructure quality effect and exports on economics growth in the Ancash region during the period 2003-2013; it studies how the road network quality has impacted over the territorial location of export industries, the regional finance, and how both, exports and finance, have impacted over the regional GDP growth rate; finally this work analyses the effect of economic growth rate over the regional poverty level. The extractive export firms are located near the sites of its natural resources (mining sites and anchovies); likewise the enterprises which export fruits and vegetables are located on the region’s coast, while there is no agriculture export company at the Callejón de Conchucos due to the lack of a road network that could make the agriculture export business a viable adventure; on the other hand, this study reveals that the Ancash region has a very rudimentary and unequal financial system because there are several provinces which have no banking offices Despite regional GDP only grew at an annual rate of 0.8% during the period 2007-2014, total poverty has suffered an important reduction, but very unequal.